Examining Job Satisfaction and Intent to Stay for Neonatal Nurse Practitioners: The Impact of Mentoring - Moss, Colleen Reilly (Advances in neonatal care, 2022)
In 2017, the National Association of Neonatal Nurse Practitioners (NANNP) recommended that organizations implement formalized mentoring programs for neonatal nurse practitioners (NNPs). There is significant evidence to support that mentoring positively impacts nurse practitioners' job satisfaction and retention. However, there is a lack of evidence-based literature specific to NNP mentoring. Determine the impact of participation in the NANNP formalized mentoring program on job satisfaction and retention for novice and experienced NNPs in an academic medical center in Tennessee. This quality improvement project utilized a secure online survey that included the Misener Nurse Practitioner Job Satisfaction Scale (MNPJSS) and 2 intent-to-stay items prior to implementation of a 6-month mentoring program. Neonatal intensive care unit nurse practitioners completed the same electronic survey at 3 intervals after program implementation to determine the impact of the mentoring program on job satisfaction and intent to stay. Project results identified a significant difference in MNPJSS scores for participants in a 6-month formal mentoring program using the NANNP tool kit. The MNPJSS scores moderately correlated with intent to stay at 1 year and strongly correlated with intent to stay at 3 years. The results of this project support the positive impact of a formalized mentoring program on job satisfaction for new graduate nurse practitioners. Recognizing the challenge to recruit and retain NNPs, organizations should explore creative solutions to develop and support formalized mentoring programs. Further research is warranted to validate use of the NANNP tool kit in the establishment and evaluation of a formalized mentoring program.Video abstract available at:https://journals.lww.com/advancesinneonatalcare/Pages/videogallery.aspx .